How digital governance networks shape community empowerment: A multilevel study of Indonesian villages - Aminullah Aminullah; Any Urwatul Wusko; Dustin Tarinque Loreño (JURNAL ILMU SOSIAL, 2026)
This study examines how digital governance networks shape community empowerment in Indonesian villages, focusing on the mediating role of participation quality and citizen facing transparency and accountability. Drawing on network governance and empowerment theory, the study conceptualizes village digitalization as an inter-organizational governance arrangement rather than a standalone administrative intervention. Quantitative data were collected from villages in East Java Province between May and July 2025, involving governance network respondents and 1,200 community members. Governance network characteristics were measured using social network analysis, while citizen perceptions of participation quality, transparency and accountability, and community empowerment were captured through structured surveys. The hypotheses were tested using multilevel structural equation modelling to distinguish village level governance effects from individual level empowerment mechanisms. The results show that higher levels of digital integration and greater network density are positively associated with participation quality and transparency at the village level, while highly centralized governance networks are associated with lower participation quality. At the individual level, participation quality and transparency and accountability are positively related to community empowerment. Mediation analysis confirms that the effects of digital integration and governance network structure on empowerment are indirect and transmitted through governance processes. The study contributes to public administration scholarship by demonstrating that digital governance reforms enhance community empowerment only when embedded within collaborative and transparent governance networks.